Perilunate Injuries: Current Aspects of Management. Issue 10 (October 2021) - Kinghorn, Alison; Finlayson, Graham; Faulkner, Alastair; Riley, Nicholas
Abstract: Perilunate dislocations (PLD) and perilunate fracture dislocations (PLFD) are high-energy injuries which can result in long-term complications and significant disability. Early identification of these injuries, followed by prompt, appropriate management is key to optimising patient outcomes. Knowledge of the carpal anatomy is essential in order to understand the varied patterns of injury and plan appropriate definitive management. Emergent reduction and close monitoring of the median nerve, followed by prompt stabilisation or repair of the injured structures remain the mainstay of treatment. In this review, we present a summary of the current evidence regarding the identification and management of these complex injuries.